Visual Field Progression in Retinitis Pigmentosa - Xu, Manlong; Zhai, Yi; MacDonald, Ian M. (Investigative ophthalmology & visual science, 2020)
To retrospectively study the rate of visual field (VF) progression in patients with retinitis pigmentosa (RP) as it relates to different targets and inheritance patterns. A total of 275 kinetic VF tests were collected from 52 subjects with RP over a period of up to 29 years (mean, 12 years). The VF areas of Goldmann targets V4e, III4e, and I4e were calculated using Photoshop. Differences in the rate of VF loss among different targets and inheritance patterns were compared. There was a significant interocular correlation in both visual acuity (VA) (R2 = 0.739, P < 0.001) and VF area (R2 = 0.815, P < 0.001). The annual rates of decline in VF area for V4e, III4e, and I4e targets were 7.5%, 10.7%, and 12.5%, respectively (all P < 0.001). All of the rates were significantly different from each other (P < 0.001). The mean rate of VF loss was 10.3% (P = 0.009) for autosomal recessive, 2.7% (P = 0.215) for autosomal dominant, and 7.2% (P = 0.009) for X-linked patterns of inheritance. However, the differences among them were not statistically significant (P > 0.05). Based on VF, survival analysis indicated that our patients failed the vision standard for driving and reached legal blindness at the median ages of 37 and 55 years, respectively. The rate of VF loss varies among targets in patients with RP. Fifty percent of patients are not qualified to drive by the age of 37 and become legally blind by the age of 55. These results can be useful for counseling patients with RP as to their potential rate of VF decline.